7th International Immunoglobulin Conference: Transplantation. (December 2014) - Jordan, S. C.; Glotz, D.
Summary: The data presented highlight the complexity of the immune response during transplantation. Early identification and characterization of donor‐specific anti‐HLA antibodies (DSAs) allows for identification of patients at high risk of transplant rejection and offers information regarding appropriate intervention strategies. The availability of new diagnostic tools can also detect the presence of complement‐binding antibodies, providing further information as to the cytotoxic potential of these antibodies. It is particularly encouraging to note that monitoring transplant recipients for the presence of various immune cells or immunoglobulin G (IgG) levels can provide detailed information regarding those at high risk for complications and therefore increased morbidity and mortality. Intervention strategies, either before or after transplantation, may potentially increase the long‐term survival of allografts, thus enhancing patient outcomes. Future trials are warranted to assess these strategies in more detail.